PENGARUH KUALITAS PELAYANAN MANASIK HAJI TERHADAP KEPUASAN JAMAAH HAJI DI KBIH AT-TAQWA KOTA TANGERANG - Amirudin Amirudin; Renaldi Rio Triantoro (Jurnal Manajemen Dakwah, 2022)
The purpose of this study was to find out the Hajj ritual services at KBIH At-Taqwa Tangerang City in 2019 and to find out how much influence the quality of services provided by KBIH At-Taqwa had on the satisfaction of pilgrims. This study uses a quantitative approach method. The sampling used the Purposive Sampling technique with a standard deviation of 10% which resulted in 56 respondents from the population of Hajj pilgrims at KBIH At-Taqwa in 2019. The results showed that there was a significant relationship between the quality of Hajj ritual services and the satisfaction of the pilgrims shown. with a T value of 2,005. The correlation value is 0.860. The value of the coefficient of determination is 0.740 which shows that 74% of pilgrims' satisfaction has an effect on the quality of service at KBIH At-Taqwa, while the other 26%. how much influence the quality of service provided by KBIH At-Taqwa has on the satisfaction of pilgrims. This study uses a quantitative approach method. The sampling used the Purposive Sampling technique with a standard deviation of 10% which resulted in 56 respondents from the population of Hajj pilgrims at KBIH At-Taqwa in 2019. The results showed that there was a significant relationship between the quality of Hajj ritual services and the satisfaction of the pilgrims shown. with a T value of 2,005. The correlation value is 0.860. The value of the coefficient of determination is 0.740 which indicates that 74% of pilgrims' satisfaction has an effect on the quality of service at KBIH At-Taqwa, while the other 26% is influenced by other variable factors.